Global characterization of the Dicer-like protein DrnB roles in miRNA biogenesis in the social amoeba Dictyostelium discoideum. Issue 7 (3rd July 2018) - Liao, Zhen; Kjellin, Jonas; Hoeppner, Marc P.; Grabherr, Manfred; Söderbom, Fredrik
ABSTRACT: Micro (mi)RNAs regulate gene expression in many eukaryotic organisms where they control diverse biological processes. Their biogenesis, from primary transcripts to mature miRNAs, have been extensively characterized in animals and plants, showing distinct differences between these phylogenetically distant groups of organisms. However, comparably little is known about miRNA biogenesis in organisms whose evolutionary position is placed in between plants and animals and/or in unicellular organisms. Here, we investigate miRNA maturation in the unicellular amoeba Dictyostelium discoideum, belonging to Amoebozoa, which branched out after plants but before animals. High-throughput sequencing of small RNAs and poly(A)-selected RNAs demonstrated that the Dicer-like protein DrnB is required, and essentially specific, for global miRNA maturation in D. discoideum . Our RNA-seq data also showed that longer miRNA transcripts, generally preceded by a T-rich putative promoter motif, accumulate in a drnB knock-out strain. For two model miRNAs we defined the transcriptional start sites (TSSs) of primary (pri)-miRNAs and showed that they carry the RNA polymerase II specific m 7 G-cap. The generation of the 3ʹ-ends of these pri-miRNAs differs, with pri-mir-1177 reading into the downstream gene, and pri-mir-1176 displaying a distinct end. This 3´-end is processed to shorter intermediates, stabilized in DrnB-depleted cells, of which some carry a short oligo(A)-tail. Furthermore, we identified 10 new miRNAs, all DrnB dependent and developmentally regulated. Thus, the miRNA machinery in D. discoideum shares features with both plants and animals, which is in agreement with its evolutionary position and perhaps also an adaptation to its complex lifestyle: unicellular growth and multicellular development.